A structural model evaluating the relationships among dining frequency, involvement, and restaurant attributes. Issue 6 (2nd November 2018) - Bardwell, Amy M.; Stephan, John T.; Rahman, Imran; Reynolds, Dennis
ABSTRACT: This study develops and tests a dining involvement model based on the involvement construct and elaboration likelihood model. Our model links the perceived importance of dining attributes with dining frequency. Using literature and factor analysis, one main dining attribute (i.e. food) and three ancillary dining attributes (i.e. service, menu, and atmosphere) were identified. The structural equation model indicated that dining frequency influenced dining involvement, which in turn influenced perceptions of the three ancillary restaurant attributes but not the main one. These results offer industry professionals evidence on maintaining repeat patronage from highly involved diners by promoting relevant restaurant features.